Novel insights on lower limb musculoskeletal health and performance in pre-adolescent and adolescent gymnasts - Bradshaw, E. J.; Le Rossignol, P.; Williams, M.; Lorenzen, C. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
New analyses are presented from the data of Bradshaw and Le Rossignol (2004) to examine the relationship between musculoskeletal health, and physical and performance qualities, with measures of leg stiffness in a group of female gymnasts. A gymnasts leg stiffness can be assessed through continuous jump (straight & bent legged) series tests, as well as from rebound jumps. Although the observations are retrospective, the study revealed a potential safe zone for ankle extensor stiffness. The gymnast with low stiffness had previously suffered a landing ankle injury; whilst four gymnasts with high stiffness had histories of take-off ankle injuries. Aside from profiling physical performance qualities, biomechanical (kinetic) testing has the potential to also aid in the assessment and management of the athlete's functional musculoskeletal health (rehabilitation, injury risk).